An integrated biomimetic array chip for high-throughput co-culture of liver and tumor microtissues for advanced anticancer bioactivity screening. Issue 14 (16th June 2020) - Hou, Yu; Ai, Xiaoni; Zhao, Lin; Gao, Zhao; Wang, Yujiang; Lu, Yingyuang; Tu, Pengfei; Jiang, Yong
Abstract : An integrated biomimetic array chip (iBAC) enables co-culture of three-dimensional (3D) liver and tumor microtissues for anticancer bioactivity screening at throughputs. Abstract : The integration of liver metabolism and hepatotoxicity evaluation for anticancer bioactivity assays in vitro is of fundamental importance to better predict the efficacy and safety of anticancer drugs. In particular, there is a lack of co-culture techniques that can fully mimic the physiological microenvironment at speeds consistent with high-throughput screening. Herein, an integrated Biomimetic Array Chip (iBAC) that enables co-culture of three-dimensional (3D) liver and tumor microtissues was developed for advanced anticancer bioactivity screening at throughputs. The iBAC consisted of two functional chips, a liver chip and a tumor chip containing a cross-shaped protrusion on the tip of a pillar array for co-culture. First, the 3D biomimetic liver microtissue on the liver chip was optimized to mimic superior liver function. Next, the constructed iBAC was evaluated for metabolism-induced anticancer bioactivity by using model prodrugs and for the effect of drug–drug interactions. Finally, the functionality of the iBAC for simultaneous evaluation of anticancer bioactivity and hepatotoxicity was verified. The iBAC exhibits superior performance in biomimetic and integrated functions as well as operationally simple and high-throughput co-culture that makes a good balance between functionality and throughput. Overall, the iBAC provides an integrated, biomimetic and high-throughput co-culture platform to complement the conventional bioactivity assay in tiered screening strategies and could be used as a secondary screening tool at the early phase of drug development.